2013
DOI: 10.1111/iwj.12039
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic wound fluids inversely influence adipose‐derived stem cell function: molecular insights into impaired wound healing

Abstract: Wound healing is a complex biological process that requires a well-orchestrated interaction of mediators as well as resident and infiltrating cells. In this context, mesenchymal stem cells play a crucial role as they are attracted to the wound site and influence tissue regeneration by various mechanisms. In chronic wounds, these processes are disturbed. In a comparative approach, adipose-derived stem cells (ASC) were treated with acute and chronic wound fluids (AWF and CWF, respectively). Proliferation and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Decreased levels of VEGF and/or bFGF, or inhibition of their activity leads to the limited migration of fibroblasts and the delay of wound healing (20,44). In the present study, rb-bFGF enhanced the protein and gene expression of VEGF and bFGF, which is similar to the results of a previous study (45). It is well known that the expression of VEGF and bFGF is increased following skin injury, particularly in the early stage of healing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Decreased levels of VEGF and/or bFGF, or inhibition of their activity leads to the limited migration of fibroblasts and the delay of wound healing (20,44). In the present study, rb-bFGF enhanced the protein and gene expression of VEGF and bFGF, which is similar to the results of a previous study (45). It is well known that the expression of VEGF and bFGF is increased following skin injury, particularly in the early stage of healing.…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that the expression of VEGF and bFGF is increased following skin injury, particularly in the early stage of healing. A previous report showed that the acute wound fluid, which is rich in VEGF and bFGF, increases the mRNA levels of VEGF and bFGF (45). Since a similar effect between MEBO and rb-bFGF in treating cutaneous excisional wounds was observed, it was concluded that MEBO promotes wound healing by increasing VEGF and bFGF production.…”
Section: Discussionmentioning
confidence: 91%
“…The ability of ASCs to proliferate and migrate was significantly hampered when treated with CWF that could lead to impaired regenerative potential of ASCs. However, the expression of growth factors (VEGF, bFGF, and MMP9) was strongly induced in CWF‐treated cells as opposed to AWF‐treated ASCs . Therefore, the use of ASC for wound healing should be considered carefully, as well as delivery methods and dosing regimen as the use of stem cells may differ depending on the wound type.…”
Section: Consideration Of Wound Types For Ascs Therapymentioning
confidence: 99%
“…In vitro migration assays on ADSC found that acute wound fluid was more chemoattractant than chronic wound fluid. Acute wound fluid has been shown to encourage ADSC proliferation while chronic wound fluid suppressed proliferation [37]. This suggests a growth factor or cytokine imbalance that impairs proper healing in chronic wounds.…”
Section: Effects Of Trauma On Stem Cellsmentioning
confidence: 99%